The Influence of Gender-Based Classroom Management on Students' Learning Achievement - Rifda Shakilla; Fatimah Ibda (International Journal of Education, Vocational and Social Science, 2025)
Student learning achievement is the main indicator of the success of the educational process that reflects students' ability to carry out learning activities in accordance with the expected achievements. Student learning achievement is influenced by many factors both internal and external such as attitudes, interests, basic abilities of students, learning strategies, and classroom management. In the context of education in Indonesia, especially in Aceh, the implementation of gender-based classroom management is one of the classroom management models that is carried out in an effort to improve learning achievement. This gender separation is in accordance with Qanun Number 23 of 2002 concerning the education system based on Islamic law, namely religious values ​​and community culture, but the effectiveness of this model of classroom management is still unknown. This study aims to determine the effect of gender-based classroom management on student learning achievement at SMAN 11 Banda Aceh. The quantitative method was used by distributing questionnaires on gender-based classroom management and learning achievement taken from report card scores given to 143 respondents, namely students through a purposive sampling technique. Data analysis using simple linear regression SPSS version 25. The results showed that the effect of gender-based classroom management on learning achievement obtained a significance value of 0.364. This finding concludes that gender-based classroom management does not have an effect on learning achievement. Therefore, an in-depth study is needed to understand the effectiveness of this strategy, especially in order to achieve optimal learning outcomes